Moderasi Ukuran Perusahaan kepada Pengaruh Utang Perusahaan dan Profitabilitas Perusahaan terhadap Nilai Perusahaan - Ruswan Nurmadi; Liza Novietta; Yani Suryani; Desi Ika; Rizki Fillhayati Rambe (Journal of Trends Economics and Accounting Research, 2022)
Creating good firm value is a very important thing that must be done by companies, especially companies that are listed on the stock exchange. The company's ability to survive, grow and compete highly depends on the interest of investors to invest in the company. Investors will of course be more interested in investing in companies with good firm value, which is reflected in the company's stock price. Companies that are included in the real estate and property industry in the Indonesia Stock Exchange, are one type of industry that attracts investors because of good development prospects in the future. The results of this research state that firm debt does not significantly affect firm value, firm profitability significantly affect firm value, firm size can strengthen the effect of firm debt and firm profitability on firm value. This research recommends that in the future, relevant research uses different research objects and different research variables, which are expected to affect firm value, to add to the literature on the importance of firm value